Ethnobotanical study of Xylopia aethiopica (Dunal) A. Rich. and its parasites of the genus Tapinanthus in Benin - Hounkpe, Francis; Idohou, Rodrigue; Mama, Adi; Vihotogbé, Romaric; Koura, Kourouma; Houehanou, Thierry; Ganglo, Cossi Jean (Ethnobotany Research and Applications, 2026)
Background: In response to climate change and the degradation of ecosystems, the promotion of indigenous knowledge is a key strategy for the sustainable conservation of biodiversity in West Africa. This study examines the variety of local knowledge and traditional practices related to X. aethiopica and Tapinanthus species. Methods: An ethnobotanical survey was conducted among 172 respondents familiar with these species in order to document their uses and the plant parts involved. Statistical analyses (Chi² test and Correspondence Analysis) revealed that ethnicity significantly influenced the distribution of knowledge and uses. Results: For X. aethiopica, the fruit was identified as the most valuable part of the plant (UV = 10). The species is mainly used for medicinal (39.4%), medico-religious (32.75%) and culinary (13.73%) purposes. In contrast, medico-religious (55.88%) and medicinal (38.73%) uses predominated for Tapinanthus spp., reflecting knowledge systems structured by the cultural heritage and ritual traditions of each ethnic group. Conclusions: These findings emphasise the richness and specificity of indigenous knowledge, highlighting its central role in conserving and sustainably using local plant resources. It is essential to document and integrate this knowledge into participatory ecosystem management policies in order to promote culturally appropriate and sustainable conservation strategies. Keywords: Ethnobotany, indigenous knowledge, Xylopia aethiopica, Tapinanthus spp., Benin, conservation.